COACHING CLINIC PENGUKURAN OLAHRAGA (KONDISI FISIK) TIM BOLA VOLI DESA CIJATI KECAMATAN SITURAJA KABUPATEN SUMEDANG - Bambang Sutiyono; Tirto Apriyanto; Muhamad Ilham (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract The purpose of Community Service in the Faculty Assisted Areas (PKM-WBUF) is the Volleyball Team in Cijati Village, Situraja District, Sumedang Regency. Service activities are carried out by providing knowledge in both theory and practice about Sports Measurement (Physical Conditions). The participants of this activity were the 17 participants of the Volleyball Team in Cijati Village, Situraja District, Sumedang Regency. Community Service Activities in the Faculty Assisted Areas (PKM-WBUF) have been carried out well. This service activity received an enthusiastic response from the activity participants. This is evident from the participation rate of the activity participants of 85% of the total athletes. The satisfaction level of participants in this service activity is very high, at 88.53%. Abstrak Tujuan kegiatan Pengabdian Kepada Masyarakat Wilayah Binaan Fakulttas (PKM-WBUF) adalah Tim Bola Voli Desa Cijati Kecamatan Situraja Kabupaten Sumedang. Kegiatan pengabdian dilakukan dengan pemberian pengetahuan baik teori maupun praktek tentang Pengukuran Olahraga (Kondisi Fisik). Peserta kegiatan ini adalah atleti Tim Bola Voli Desa Cijati Kecamatan Situraja Kabupaten Sumedang sebanyak 17 peserta. Kegiatan Pengabdian Kepada Masyarakat Wilayah Binaan Fakulttas (PKM-WBUF) telah terlaksana dengan baik. Kegiatan Pengabdian ini mendapatkan respon yang antusias dari para peserta kegiatan. Hal ini terbukti dari tingkat partisipasi peserta kegiatan sebesar 85% dari total atlet. Tingkat kepuasaan peserta kegiatan pengabdian ini sangat tinggi yaitu sebesar 88,53%.